Effects of Rapid Maxillary Expansion on Nocturnal Enuresis: A Literature Review (Acta Medica Academica, 2007)
Rapid maxillary expansion (RME) is a dentofacial orthopedictreatment procedure which has been routinely used to correcttransversal maxillary skeletal and/or dental constriction.Application of RME not only expands the constricted maxillabut also results in an increase in nasopharyngeal airwaydimensions, improvement in nasal respiration in patientswith abnormal breathing patterns, and better blood oxygensaturation. It is known that adenotonsillectomy significantlyreduces nocturnal enuresis in patients having upper airwayobstruction and/or breathing problems. Some authors haveshown that RME was also effective on reducing or ceasingnocturnal enuresis (bed-wetting) in patients with maxillaryconstriction. The results of these uncontrolled clinical trialsshowed that the success rate of the treatment varied from 47percent to 100 percent The purpose of this article is to reviewthe etiology and pathophysiology of nocturnal enuresis andthe studies investigating the effects of RME on nocturnal enuresisin growing children.
Keywords: Rapid maxillary expansion; Nocturnal enuresis; Nasal breathing